Morpho-genetic Diversity and Traits’ Relationship in Castor Germplasm - OKE, C. O. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Adequate knowledge of the extent of dissimilarity among germplasm accessions and traits’ relationships are of great importance in active breeding programme. In the present study, genetic diversity and traits’ relationship were assessed among 74 castor germplasm accessions collected at the National Cereals Research Institute Badeggi, Nigeria. The accessions were evaluated on replicated plots of 7.5m2 size, arranged in a randomized complete block design. The data were taken on 20 individual plants, using standard castor descriptors. The results revealed significant variations for all the traits studied among the entries. Phenotypic and genotypic coefficients of variation estimated showed low environmental effects on the observed variations. High (≥ 70%) broad sense heritability coupled with high (≥ 20%) genetic advance as percentage of mean were observed in all the traits except days to days to first raceme maturity, number of leaf lobes and seed yield. Six cluster groups, with 4 to 38 members, were identified among the accessions. Significant positive correlations were observed between the seed yield and leaf length (0.269*), and spike length (0.972**). The partitioning of the correlations into direct and indirect yield contributors showed positive direct effects for number of internodes to first raceme, spike length and height to first raceme. The findings showed that selection for long spike early accessions could result in constituting a high yielding breeding population. The identified superior accessions could serve as good germplasm sources for castor breeding programme in Nigeria.